2020
DOI: 10.1186/s12969-020-00424-x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus treatment plans for periodic fever, aphthous stomatitis, pharyngitis and adenitis syndrome (PFAPA): a framework to evaluate treatment responses from the childhood arthritis and rheumatology research alliance (CARRA) PFAPA work group

Abstract: Background: Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome is the most common periodic fever syndrome in children. There is considerable heterogeneity in management strategies and a lack of evidence-based treatment guidelines. Consensus treatment plans (CTPs) are standardized treatment regimens that are derived based upon best available evidence and current treatment practices that are a way to enable comparative effectiveness studies to identify optimal therapy and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 29 publications
0
46
1
6
Order By: Relevance
“… 43 Amarilyo et al found that the majority of physicians use 1 mg/kg of prednisone to treat attacks, and recommend increasing to 2 mg/kg in the case of frequent fever flares or incomplete response to the lower dose. 15 The fever episode is usually aborted within hours, with a minority of patients requiring a second dose 8–12 h later. Other symptoms, such as aphthous ulcers, may subside more slowly.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“… 43 Amarilyo et al found that the majority of physicians use 1 mg/kg of prednisone to treat attacks, and recommend increasing to 2 mg/kg in the case of frequent fever flares or incomplete response to the lower dose. 15 The fever episode is usually aborted within hours, with a minority of patients requiring a second dose 8–12 h later. Other symptoms, such as aphthous ulcers, may subside more slowly.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Recently PFAPA CTPs were published by an international group of researchers from the CARRA (Childhood Arthritis and Rheumatology Research Alliance) PFAPA work group. 15 …”
Section: Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ein Konsens bezüglich Dosierung und Therapiedauer besteht nicht, da die Erkrankung in der Regel selbstlimitierend verläuft. Vorgeschlagen wird eine Schubprophylaxe mit 0,5–1,25 mg Colchicin pro Tag [ 50 ].…”
Section: Indikationen Anwendungsgebiete Und Dosierungunclassified